Konsep Zinah dalam Al-Qur'an (Aplikasi Semiotika Roland Barthes terhadap QS. Al-Kahfi Ayat 7) - Subaidah, Subaidah (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The purpose of research is revealing concept of 'Zinah' from Al-Kahfi verse 7 and connecting with society now. The kinds of research are research of bibliography with a qualitative method and using semiotical analysis by Roland Barthes because it needs structural analysis in critical text. Properly, semiotical theory of Roland Barthes is two steps. First is Linguistic system or Denotation system. Second is Mythological system or Connotation system. From the connotation system will be found the mythical meaning. The result of research of linguistic system or denotation system is the word 'Zinah' translated jewelry or thing that makes the other thing becoming the beautiful. In the mythical system it is all of the things created by Allah in the earth earth including mountains, trees, seas, rivers, plants and animals that makes the earth look beautiful. Behind this beauty, Allah makes it challenging. So that from the mythical system, it can be taken the meaning of myth from the word 'Zinah', it is jewelry that properly, it is used by a girl community and have a highly precious value such as necklace, ring, armlet and others made by gold or silver. This research suggests further studying the meaning of 'Zinah' in the Al-Qur'an in QS. Al-Kahf verse 7 uses semiotic theories or other linguistic theories. Especially the theory of semiotics which can reveal a deeper meaning to the word meaning of 'Zinah'.